Obesity promotes immunotherapy efficacy by up-regulating the glycolytic-mediated histone lactacylation modification of CD8+ T cells - Wang, Kai-Xuan; Shi, Dong-Min; Shi, Xiao-Li; Wang, Jing-Yuan; Ai, Xing-Hao (Frontiers in Pharmacology, 2025)
The response rate of immune checkpoint blockade (ICB) therapy for non-small-cell lung cancer (NSCLC) remains limited. Recent evidence suggests that obese cancer patients are more likely to benefit from ICB therapy, however, the specific mechanism needs further research. In this study, we found that anti-PD-1 therapy was more effective in obese NSCLC patients compared to normal weight patients and this was verified in mouse NSCLC model. Further bioinformatics analysis indicated that the glycolytic metabolism was markedly elevated in obese NSCLC patients. In vitro co-culture experiment showed that both increased glycolysis of tumor cells and external addition of lactate promoted T cell PD-1 expression. And, PD-1 upregulation was related to monocarboxylate transporter 1 (MCT1)-mediated lactate transport and subsequent lysine lactylation of histones in T cells. Based on the aforementioned data, our study contributes to better application of anti-PD-1 therapy in NSCLC.